Pengaruh investasi dan tenaga kerja terhadap PDRB sektor pertambangan di Kabupaten Bungo - Habibullah, Habibullah; Tan, Syamsurijal; Artis, Dearmi (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
This study aims to determine the development and contribution of investment, labor, and GRDP in the mining sector of Bungo Regency and the effect of investment and work on the GRDP of the mining sector in Bungo Regency. The analytical method used is multiple linear regression with Ordinary Least Square (OLS). The results of this study indicate that, during the period 2008-2017, investment, labor, and GRDP of the mining sector in Bungo Regency experienced fluctuating developments, with an average GRDP of the mining sector 12.7 percent, investment of 29.8 percent per year, and 2,6 percent of the workforce. The investment contribution to the mining sector has an average annual rate of 45.2 percent. The regression results show that the independent variables simultaneously affect investment and labor on the dependent variable. Meanwhile, partially the workforce impacts GRDP while acquisition does not occur during the period 2008-2017. Keywords : Investment, Labor, GDP mining sector